Short term side effects of inactivated COVID-19 vaccines among Pakistani population: a survey-based cross-sectional study - Nawaz, Zunaira; Zahid, Mariyam; Sajjad, Mariam; Azhar, Naveen; Hasan, Noor ul Elmah; Shaukat Siddiqui, Arooma (Journal of the Pakistan Medical Association, 2023)
Objective: To assess the short-term adverse effects of two inactivated coronavirus disease-2019 vaccines, and the demographic factors associated with such events. Method: The cross-sectional study was conducted in Karachi from August to October 2021 after approval from the ethics review board of Dow University of Health Sciences, Karachi, and comprised adults of either gender who had received at least one dose of either Sinopharm or CoronaVac vaccine. Data was collected using a predesigned online and printed survey forms. The questionnaire investigated the symptoms experienced by the participants after the administration of the vaccine dose. Data was analysed using SPSS 22. Results: Of the 1000 survey forms filled, 896 were analysed; 505(56.4percent) women and 391(43.6percent) men were included in the study. Most of the participants were aged 18-30 years 644(71.9percent). Overall, 581(64.8percent) subjects had received Sinopharm vaccine, and 315(35.2percent) received CoronaVac. The incidence of side effects after the first and second dose respectively was 63.3percent (368 out of 581) and 55.2percent (239 out of 433) for Sinopharm and 65.4percent (206 out of 315) and 61.4percent (89 out of 145) for CoronaVac. The factors associated with a higher risk of side effects were female gender and young age (p 0.05). Conclusion: Most of the reported symptoms were minor in nature, like pain at the injection site, and women and those of young age reported such symptoms more than men and the elderly. Key Words: COVID-19 vaccine, Side effects, Sinopharm, CoronaVac, SARS-CoV-2.